Study of gonadotropin (GtH) stimulating hormone on gonad maturation of climbing perch Anabas testudineus Bloch - Suriansyah, .; Junior, M. Zairin; Sudrajat, Agus Oman (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
Gonadotropin can quicken the process of 17α-hidroxyprogesterone hormone synthesis becoming 17α, 20β-di hidroxyprogesterone as the maturation inducing steroids (MIS) and quicken the process of egg nucleus integration to germinal vesicle breakdown (GVBD) position. This research aimed to know the efficacy of gonadotropin hormone in the form of ovaprim on gonad maturation of climbing perch (Anabas testudineus Bloch). Stimulation of GtH with a dose of 0.5 ml/kg of fish body weight could improve the fish gonado somato index (GSI) to 2.72 %, improve the the final egg diameter to 0.70 mm (71.50 %), and shorten ovulation time which down to 4.30 hours. Key words: Gonadotropin hormone, gonad maturation, Anabas testudineus ABSTRAK Hormon gonadotropin dapat mempercepat proses sintesa hormon 17α-hidroksiprogesteron menjadi 17α, 20β-dihidroksiprogesteron yang berfungsi sebagai steroid yang merangsang pematangan gonad dan mempercepat proses integrasi inti sel telur menuju posisi germinal vesicle breakdowan (GVBD). Penelitian ini bertujuan untuk mengetahui efektivitas hormon gonadotropin yang terdapat dalam ovaprim terhadap pematangan gonad ikan betook Anabas testudineus Bloch. Pemberian hormon GtH dalam bentuk ovaprim dengan dosis 0,5 ml/kg bobot ikan dapat memperbaiki perkembangan gonad yang ditunjukkan dengan peningkatan nilai gonado somatik indeks (GSI) sebanyak 2,72%, peningkatan diameter telur menjadi 0,77 mm (71,50%) dan mempercepat waktu ovulasi menjadi 4,3 jam. Kata-kata kunci: Hormon gonadotropin, pematangan gonad, ikan betok